ELUSIDASI STRUKTUR MOLEKUL UK-3, UK-4 DAN UK-5, SENYAWA BIOAKTIF DARI Streptomyces sp. 517-02. - Muhammad Hanafi (Research Center for Chemistry - LIPI, 1998)
New potential antifungal antibiotics UK-2A, B, C and D were elucidated as nine membered dilactone derivatives, isolated from mycelial cake of an actinomycete strain 517-02. In the continuation of a screening program in order to discover other useful bioactive metabolites from the same microbial sources, a novel UK-3 and two known compounds of UK-4 and UK-5 have been isolated.The molecular structure of UK-3 was very similar to UK-2A, except thai UK-3 did not have any methoxy group (-OCH3) on pyridine at ('-4'. UK-4 and UK-5 were identified as kown compounds of isocoumarine. These structures were elucidated based on their spectral and chemical evidence.Biological activity assay, demonstrated that UK-3 was active as against to Saccharomyces cerevisiae, Aspergillus niger dan Neurosporo sitophila and inhibited growth of cancer cell, P-388, B-16, KB and COLO-201.